Religion, Work Ethics, and Business Attitude: A Case Study on the Meaning of Business Behavior of Madurese Fruits Traders in Malang - Djakfar, Muhammad (Accounting Department,, 2007)
Islam is a source of motivation to build work ethics and direct the behavior of businessmen. Madurese people are recognized as one of the wandering. ethnics. They are usually good adherence of Islam and tough traders. However, they are often regarded as people who do not really care of ethical values. Based on such characteristics, this dissertation examines their business behavior according to the ethical norms in Malang. There are three aspects that will be explored in this dissertation: (1) the meaning of business ethics, (2) how the traders construct the ethics, and (3) how the traders implement ethics in business activities. Qualitative approach is used to understand this phenomenon. In-depth interview, participatory observation, and documentation were employed to obtain the data. The data were analyzed and interpreted by using social construct analysis. The study shows that pancengan (honest) traders argued that ethical values should be maintained and respected but does not need to be involved in the area of business. For those who do not want to be involved in pancengan, however, ethics was an impoitant requirement in order to obtain the wealth blessed by God. Thus, ethics and business are inseparable. The meaning of ethics was produced from dialectical conditions between their culture and Islamic religious values. How to implement? lt can be understood that the relationship among traders was built because of their feelings of being together, caring, and less competitive. This is induced by the fact that some of them were relatives, or coming from the same place. The traders with pancengan principle tend to be involved in manipulation. For non-pancengan traders, however, they attempt to minimize dishonesty. Both of the groups have positive concern toward their environment; this attitude seems to be inï¬‚uenced by religious values and the government regulation. Keywords: religion, work ethics, business attitude, case study, the meaning of business ethics, traders, Madurese ethnics in Malang